Clinical significance of inferior ST elevation during acute anterior myocardial infarction. Issue 6 (December 1995) - Tamura, A.; Kataoka, H.; Nagase, K.; Mikuriya, Y.; Nasu, M.
Abstract : OBJECTIVES–To clarify the genesis and clinical significance of inferior ST elevation during acute anterior myocardial infarction. PATIENTS AND DESIGN–A total of 106 patients with first acute anterior myocardial infarction (< or = 6 h) were divided into two groups according to the presence (group A, n = 12) or absence (group B, n = 94) of ST elevation of > or = 1 mm in at least two of the inferior leads on the admission electrocardiogram. RESULTS–On admission electrocardiograms, group A had a smaller summed ST deviation in the lateral limb leads than group B. On emergency coronary arteriograms, the incidence of a wrapped left anterior descending artery was higher in group A than in group B (100% v 27%, P < 0.01). The incidence of occlusion of a left anterior descending artery distal to its first diagonal branch was higher in group A than in group B (100% v 46%, P < 0.01). Peak serum creatine kinase activity and in-hospital mortality tended to be lower in group A than in group B. Group A had better left ventricular ejection fraction and regional wall motion in the anterobasal and anterolateral regions in the chronic phase than group B. In contrast, regional wall motion in the diaphragmatic region was reduced to a greater extent in group A than in group B. CONCLUSIONS–Inferior ST elevation during acute anterior myocardial infarction appears only in the presence of a combination of a lesser degree of transmural ischaemic myocardium in the anterobasal and anterolateral wall together with transmural ischaemic myocardium in the inferior wall; in all cases there was occlusion of a wrapped left anterior descending artery distal to its first diagonal branch. Patients with such an ST elevation appear to have a better in-hospital prognosis than those without it.